Radiation spectrum of an electron moving in a spiralin medium - Konstantinovich, A.V.; Konstantinovich, I.A. (Condensed Matter Physics, 2007)
The action of the Doppler effect on the particularities of radiation power spectral distribution of an electron moving in a spiral in a medium has been investigated near the Cherenkov threshold. The fine structure of the electromagnetic radiation spectrum at the Cherenkov threshold and the synchrotron-Cherenkov radiation spectrum for an electron moving along a spiral with non-relativistic longitudinal component of the velocity (i.e., the component parallel to the magnetic induction vector) in a transparent isotropic medium have been obtained and studied. Дослiджено вплив ефекту Доплера на особливостi спектрального розподiлу потужностi випромiнювання електрона, що рухається вздовжгвинтової лiнiї у середовищi, поблизу черенковського бар’єру. Отримана i дослiджена тонка структура електромагнiтного спектра на черенковському бар’єрi та спектра синхротронно-черенковського випромiнювання електрона, що рухається вздовж гвинтової лiнiї у прозорому середовищi, з нерелятивiстською поздовжньою компонентою швидкостi (компонентою, що паралельна вектору магнiтної iндукцiї).